Suchodolski, Siegmund von 1876 - 1935 Reichsparteitag der NSDAP 1-3... - Siegmund von Suchodolski (Wikimedia Commons, 1933)
Carte postale ancienne issue de Wikimedia Commons. Titre: Suchodolski, Siegmund von 1876 - 1935 Reichsparteitag der NSDAP 1-3 September 1933 Nürnberg Ansichtskarte Nazi Propaganda Picture postcard 693363-000000. Reichsparteitag der N.S.D.A.P. 1.3. September 1933 Nazi Party Propaganda postcard for the 5th Party Congress, the "Rally of Victory" (Reichsparteitag des Sieges), held in Nuremberg, August 30 September 3, 1933. Painting by German commercial artist Siegmund von Suchodolski showing Nazi swastika party flags before the Nuremberg Castle. Text in fraktur typeface.
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château